A regulação no contexto hospitalar enquanto ferramenta gerencial: a compreensão dos profissionais envolvidos - Rodrigues, Luciane Cristine Ribeiro [UNESP] (2013)
The need the access so according to the principles and guidelines of the Health Policy and considering the current context of using the hospital beds, related to insufficient offer related to demand, arises the need to think of innovative proposals that management contemplate such expectations proposed by the Unified Health System, and consequently attend the real needs of health of the population, providing a comprehensive and timely integral. In this context, what is questioned is whether the installation of the Health care coordination and monitoring as a tool for management, improvement occurred in equating the beds? The objectives were to understand the perception of managers on the process of elaboration, implementation and deployment of NIR; to know the perception of doctors and nurses working in the NIR on its deployment and operation; understand the weaknesses and potential of the NIR already deployed, from the perception of doctors and nurses, who experience the regulation of t beds in HC institute. The survey results show that despite the difficulties, there is a considerable impact of this service in the management of beds and room, and consequently in hospital management, however we call the attention to the need for integration in the health system, with the sharing of innovative proposals management, aiming at overcoming the weaknesses in the health system, in order to provide a continuous and integral care